DORISEA: Dynamiken von Religion in Südostasien (Georg-August-Universität Göttingen, Institut für Ethnologie, 2012)
[Dt.:] Das Kompetenznetz “Dynamiken von Religion in Südostasien” (DORISEA) ist ein durch das Bundesministerium für Bildung und Forschung (BMBF) geförderter Forschungsverbund, der am Institut für Ethnologie der Universität Göttingen koordiniert wird. Wissenschaftlerinnen und Wissenschaftler der Universitäten Göttingen, Hamburg, Münster, Heidelberg und Berlin (HU) untersuchen in mehreren Projekten den Zusammenhang von Religion und Moderne in Südostasien. [Engl.:] The competence network "dynamics of religion in Southeast Asia" (DORISEA) is a research network funded by the German Federal Ministry for Education and Research (BMBF) and coordinated by the Departement of Social and Cultural Anthropology at the University of Göttingen. Scientists from the Universities of Göttingen, Hamburg, Münster, Heidelberg and Berlin (Humboldt University) are involved in several projects that investigate the relationship between religion and modernity in Southeast Asia.
Keywords: Website